The Proposition of the Pulmonary Route as an Attractive Drug Delivery Approach of Nano-Based Immune Therapies and Cancer Vaccines to Treat Lung Tumors - Donkor, Michael; Jones, Harlan P. (Frontiers in Nanotechnology, 2021)
Lung cancer is the leading cause of cancer related deaths globally, making it a major health concern. The lung’s permissive rich microenvironment is ideal for supporting outgrowth of disseminated tumors from pre-existing extra-pulmonary malignancies usually resulting in high mortality. Tumors occurring in the lungs are difficult to treat, necessitating the need for the development of advanced treatment modalities against primary tumors and secondary lung metastasis. In this review, we explore the pulmonary route as an attractive drug delivery approach to treat lung tumors. We also discuss the potential of pulmonary delivery of cancer vaccine vectors to induce mucosal immunity capable of preventing the seeding of tumors in the lung.